PAYUNG HUKUM PENYANDANG DISABILITAS DALAM KONTEKS DUKUNGAN DAN AKSESIBILITAS TERHADAP PEMBANGUNAN SOSIAL BERKELANJUTAN - Muhammad Ramadhana Alfaris (Universitas Widya Gama Malang, 2018)
Disability is a condition experienced by a person with various kinds of physical limitations. The thing of unfair is a sensitive part for people with disabilities, starting from discrimination, less of support, community stigma, and many inadequate access for people with disabilities. Therefore, the identification of problems in this study discusses the legal umbrella for persons with disabilities as well as support and accessibility to sustainable social development. This study uses descriptive analytical methods to explain the existing situation by using a normative juridical approach to identify and examine the law. The result is there are still many discriminatory attitudes towards persons with disabilities, such as from education access that is not yet the totality of persons with disabilities, then economic access for people with disabilities is less considered, then in health access that is still not fulfilled, especially health against physical disabilities, and less education of political access access for people with disabilities.Kata Kunci: payung hukum disabilitas, dukungan, aksesibilitas, pembangunan sosial.